MENINGKATKAN KEMAMPUAN KOGNITIF ANAK MELALUI METODE ROLE PLAY DI TK LAHILA DONGGO - Imaniar, Mahrati; Yakin, Nur Rahayul; Anggryani, I'in; Roswati, Roswati (Early Stage, 2025)
The independent variable is one that alters or impacts the existence of the dependent variable, whereas the dependent variable is one that is affected by or the cause of the independent variable's existence. Since peer contact is a setting where people build their character through both positive and negative behavior, it may be claimed that peer interaction has a substantial impact on students' religiosity. Religion's approach to peer interaction also strongly inspires people to attempt and strive for their goals because, without prayer and worship, effort alone would not yield the greatest outcomes. Thus, in this role play, children are allowed to participate directly in the activity. There are types of games carried out in this role play, namely children playing puzzles, dismantling picture pieces and arranging wooden blocks that have been provided.